MOTIVATING CHINESE MILLENNIALS: POST-80S AND -90S EMPLOYEES IN STATE-OWNED BANKS IN NANNING, CHINA - Liao, Shi Zhu (2016)
The millennial employees is progressively emerging into essential force of every organization nowadays, hence, their job satisfaction and motivation should be paid more attentions to by every employers. This issue is particularly significant in a southwestern city of China—Nanning, in which with increasingly shortages of the financial talents, the millennial labor become the rage at the labor market. This dissertation focuses on studying how to better manage the Chinese millennials in state-owned banks in Nanning, China.